1986
DOI: 10.1111/j.1365-2133.1986.tb06654.x
|View full text |Cite
|
Sign up to set email alerts
|

Release of prostaglandin D2 and histamine in a case of localized heat urticaria, and effect of treatments

Abstract: A case of localized heat urticaria in a 70-year-old woman is reported. Increased plasma levels of prostaglandin D2 and blood histamine after heat challenge indicate a role for mast cell degranulation in the pathophysiology of the syndrome. Treatment with astemizole increased the temperature threshold to wealing, but not to itch or erythema. The patient was partially desensitized by repeated exposure to heat and this was further improved by indomethacin. After treatment there was no increase in plasma prostagla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 16 publications
(21 reference statements)
4
40
0
Order By: Relevance
“…Although PGD2 potentiates the increase in vascular permeability due to histamine in rat skin (Flower et al, 1976) there is no evidence for the potentiation of the wheal (Barnes & Heavey, 1986) erythema, or increased blood flow (Maurice et al, 1987) due to histamine injection in human skin. The relative proportions of histamine and PGD2 found in this study are similar to the ratio in blood draining whealed skin in immediate cold and heat urticaria (Heavey et al, 1986a;Koro et al, 1986) and we conclude that PGD2 has at best a minor role in immediate allergic reactions in skin.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Although PGD2 potentiates the increase in vascular permeability due to histamine in rat skin (Flower et al, 1976) there is no evidence for the potentiation of the wheal (Barnes & Heavey, 1986) erythema, or increased blood flow (Maurice et al, 1987) due to histamine injection in human skin. The relative proportions of histamine and PGD2 found in this study are similar to the ratio in blood draining whealed skin in immediate cold and heat urticaria (Heavey et al, 1986a;Koro et al, 1986) and we conclude that PGD2 has at best a minor role in immediate allergic reactions in skin.…”
Section: Discussionsupporting
confidence: 60%
“…PGD2 and PGE2 were analysed by radioimmunoassay (RIA) as their methyloximate derivatives by methods similar to those previously described Koro et al, 1986). Briefly, each 0.2ml sample was mixed with 0.2ml of methyloximating reagent (methoxyamine hydrochloride 0.12mM, sodium acetate 1.OM and ethanol 10% v/v, pH 5.6-5.8) and incubated either at 60°C for 30 min or at room temperature overnight.…”
Section: Radioimmunoassay Ofprostaglandins D2 and E2mentioning
confidence: 99%
See 2 more Smart Citations
“…Lung mast cells generate prostaglandin D2 (PGD2) in vitro following calcium ionophore A23 187-and IgE-dependent activation (Holgate et al, 1984). Evidence ofPGD2 generation by human skin derives from experiments in vivo in which local provocation of cold or heat urticaria and anaphylaxis is accompanied by a rise in venous plasma histamine or PGD2 concentrations (Heavey et al, 1986;Koro et al, 1986;Barr et al, 1986). The precise function of released PGD2 in the skin is not known, although recent studies have shown it to be a weak vasodilator in the human cutaneous vasculature (Beasley et al, 1987) and it is also a weak chemokinetic agent in human leukocytes (Goetzl et al, 1976) causing neutrophil accumulation when injected 'Author for correspondence at: Clinical Pharmacology, CF104, Centre Block, Southampton General Hospital, Southampton S09 4XY. intradermally (Soter et al, 1983).…”
Section: Introductionmentioning
confidence: 99%